PERSEPSI GURU TERHADAP IMPLEMENTASI PEMBELAJARAN TEMATIK INTEGRATIF KURIKULUM 2013 DI SEKOLAH DASAR MUHAMMADIYAH - Risminawati, Risminawati; Fadhila, Nurul (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this study was to describe the perception of teachers towards the preparation of the implementation of an integrated thematic learning curriculum in 2013 and the perception of teachers towards the implementation of integrated thematic curriculum in 2013 in SD Muhammadiyah Surakarta 24. The research is a qualitative research study design used is phenomenological. The technique of collecting data through observation, interviews and documentation. For the validity of the source data using triangulation and triangulation techniques.It can be concluded that the perception of teachers towards the preparation of the implementation of an integrated thematic learning curriculum in 2013 is to prepare and understand the student book and teacher books before doing the learning. RPP to make some adjustments tailored to the needs of learners. Providing tools and learning media to be used. The media being used does not have any teachers make instructional media, teachers to sort out which material that is considered difficult requiring the use of instructional media, and perceived easy not to use instructional media. Prepare assessment instruments. Perception of teachers on the implementation of thematic learning integrative curriculum in 2013 that the learning has been interesting, learning students are invited active discussion, ask questions so that learning is not only one way, by learning to use the themes in the study, so that the learning can be achieved many learning objectives, learning teacher led to create lesson plans in advance, so that during the learning process the teacher already knows what needs to be done to facilitate the teacher to make a step in teaching.